The rivalrous Renaissance - Irish, Bradley J., author.
1 online resource.
Keywords: "Envy and jealousy are the emotions that fuel interpersonal rivalry, and interpersonal rivalry is a cornerstone of literature. Emerging from growing scholarly interest in the history of emotion, The Rivalrous Renaissance is the first full-length study of envy and jealousy in Renaissance England. The book introduces readers both to the cultural dynamics of affective rivalry in the period, and to how these crucial feelings inspired literary works across a wide range of genres, by luminary authors such Philip Sidney, Edmund Spenser, Mary Wroth, William Shakespeare, and John Milton. Early modern concepts of envy and jealousy were more actively theorized as central components of human experience than is typical today. Irish argues that literature is the key domain where this Renaissance theorization of affective rivalry was brought to life. Poetry, drama, and narrative prose created the conditions for these concepts to become most socially meaningful, simulating the interpersonal experiences in which the emotions practically manifest. This volume will appeal to scholars interested in the history of emotion and affect, as well as more broadly to scholars of the literature and social dynamics of early modern England, and to undergraduate and graduate students in specialized seminars"--